Eastern Region Transport Survey Volume V Part I : Ports and Shipping - Planning Commission (Planning Commission, 1967)
Background: Calcutta is a tidal river port located on the East bank of the Hooghly River, 126 miles from the sea, where it was established in 1690, Around 1880, when its capacity consisted of 4 screw pile jetties (8 berths), the port started to grow to its present shape by construction of’ the Calcutta jetties' in 1880, Kidder docks in 1884, the Petroleum wharf at Budge Budge in 1886, The Garden Reach jetties in 1925, the King George Dock in 1928, and by further improvements of the port layout.
Planning Commission Government of India
Planning Commission Government of India